2008
DOI: 10.1007/s11295-008-0169-6
|View full text |Cite
|
Sign up to set email alerts
|

Congruence between environmental parameters, morphology and genetic structure in Australia’s most widely distributed eucalypt, Eucalyptus camaldulensis

Abstract: Eucalyptus camaldulensis is one of the most widely utilised eucalypts. It is also the only eucalypt that occurs across the Australian continent, playing a key ecological role as fauna habitat and in riverbank stabilisation. Despite its ecological and economic importance, uncertainty remains regarding the delineation of genetic and morphological variants. Nine hundred and ninety trees from 97 populations, representing the species' geographic range were genotyped using 15 microsatellite loci and patterns of dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
87
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(97 citation statements)
references
References 45 publications
7
87
1
2
Order By: Relevance
“…The development of microsatellite primers for eucalypt taxa (Brondani et al 1998(Brondani et al , 2006Byrne et al 1996;Glaubitz et al 2001;Jones et al 2001;Ottewell et al 2005;Shepherd et al 2006;Steane et al 2001;Thamarus et al 2002) opened the door for reliable genome-wide genotyping of a relatively large number of samples. Microsatellite markers gave researchers the power to examine genetic relationships within and among populations of one (e.g., Butcher et al 2009;Elliott and Byrne 2003;Jones et al 2007;Payn et al 2008;Rathbone et al 2007;Walker et al 2009; see also Byrne 2008 and references therein) or a few closely related species (e.g., Holman et al 2003, Le et al 2009, Shepherd et al 2008. While microsatellites were developed initially for mapping and population genetic studies, Ochieng et al (2007b) found them helpful for phylogenetic resolution of eucalypt genera.…”
Section: Introductionmentioning
confidence: 99%
“…The development of microsatellite primers for eucalypt taxa (Brondani et al 1998(Brondani et al , 2006Byrne et al 1996;Glaubitz et al 2001;Jones et al 2001;Ottewell et al 2005;Shepherd et al 2006;Steane et al 2001;Thamarus et al 2002) opened the door for reliable genome-wide genotyping of a relatively large number of samples. Microsatellite markers gave researchers the power to examine genetic relationships within and among populations of one (e.g., Butcher et al 2009;Elliott and Byrne 2003;Jones et al 2007;Payn et al 2008;Rathbone et al 2007;Walker et al 2009; see also Byrne 2008 and references therein) or a few closely related species (e.g., Holman et al 2003, Le et al 2009, Shepherd et al 2008. While microsatellites were developed initially for mapping and population genetic studies, Ochieng et al (2007b) found them helpful for phylogenetic resolution of eucalypt genera.…”
Section: Introductionmentioning
confidence: 99%
“…E. camaldulensis ssp. obtusa is the most widespread eucalypt in subtropical Australia (Butcher et al, 2009). Exploiting this ecological contrast, we empirically tested the hypothesis that constitutive isoprenoid emission is driven by ATP and NADPH availability (Loreto and Sharkey, 1993;Niinemets et al, 1999) and could potentially compete for the same with carbon assimilation (Harrison et al, 2013;Morfopoulos et al, 2014).…”
mentioning
confidence: 99%
“…For example, the spread of E. camaldulensis as an invasive weed along perennial, seasonal and intermittent watercourses in South Africa has often been reported (see, for example, Rejmánek and Richardson 2011). However, genomic research on 990 trees from 97 E. camaldulensis populations across the natural distribution in Australia has shown that genetic similarity was greatest between the nearest populations, regardless of whether or not they occurred on the same river system (Butcher et al 2009).…”
Section: Alternative Dispersal Methodsmentioning
confidence: 99%